2006
DOI: 10.1007/s00109-006-0093-x
|View full text |Cite
|
Sign up to set email alerts
|

The methionine synthase reductase 66A>G polymorphism is a maternal risk factor for spina bifida

Abstract: The methionine synthase reductase (MTRR) enzyme restores methionine synthase (MTR) enzyme activity and therefore plays an essential role in homocysteine remethylation. In some studies, the 66A>G polymorphism in the MTRR gene was associated with increased neural tube defect (NTD) risk. Using a case-control design, we studied the association between the MTRR 66A>G polymorphism and spina bifida risk in 121 mothers, 109 spina bifida patients, 292 control women, and 234 pediatric controls. Possible interactions bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 29 publications
1
32
0
1
Order By: Relevance
“…In earlier work, we identified a very common polymorphism in the methionine synthase reductase (MTRR) gene, c.66A→G (p.I22M), which is present in the homozygous state in approximately 25% of North Americans and Europeans [9]. This mutation, which affects the interaction between methionine synthase and methionine synthase reductase [10], has been examined in several clinical reports as a risk factor for NTD, with positive associations in some but not all studies [9,11,12]. However, few clinical studies have investigated the association between MTR/MTRR/ vitamin B 12 and risk for CHD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In earlier work, we identified a very common polymorphism in the methionine synthase reductase (MTRR) gene, c.66A→G (p.I22M), which is present in the homozygous state in approximately 25% of North Americans and Europeans [9]. This mutation, which affects the interaction between methionine synthase and methionine synthase reductase [10], has been examined in several clinical reports as a risk factor for NTD, with positive associations in some but not all studies [9,11,12]. However, few clinical studies have investigated the association between MTR/MTRR/ vitamin B 12 and risk for CHD.…”
Section: Introductionmentioning
confidence: 99%
“…This mutation, which affects the interaction between methionine synthase and methionine synthase reductase [10], has been examined in several clinical reports as a risk factor for NTD, with positive associations in some but not all studies [9,11,12]. However, few clinical studies have investigated the association between MTR/MTRR/ vitamin B 12 and risk for CHD. The only study to examine the effect of MTRR polymorphisms concluded that neither maternal nor case genotype significantly affected risk [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies reported gene-gene interactions with the MTHFR C677T genotype [ 92 , 103 ], other studies found a protective effect for the MTHFR 1298 C allele [ 104 , 105 ]. In addition, the MTRR 66GG genotype in the mothers was associated with a 2.1-fold (OR 2.1, 95% CI 1.3 -3.3) higher risk for having a child with NTD [ 106 ]. The MTR A2756G, the MTRR A66G [ 107 ], and the MTHFD1 1958AA polymorphisms [ 108 ] were also reported to enhance the maternal risk of having a child with spina bifida [ 28 , 107 ].…”
Section: Common Polymorphisms Associated With Neural Tube Defectsmentioning
confidence: 99%
“…MTR 2756GG genotype is an inherited vascular risk factor in the pathogenesis of sudden sensorineural hearing loss (26). Maternal polymorphisms in the MTR gene may put the fetus at increased risk for birth defects, such as spina bifi da; heart defects and preterm delivery (18,87,88).…”
Section: Good Markers For Bad Conditions -Choosing the Tools To Fi Ghmentioning
confidence: 99%